Metabolic reprogramming of CAR T cells: a new frontier in cancer immunotherapy - Frlic, Tjaša; Pavlin, Mojca (Frontiers in Immunology, 2025)
Chimeric Antigen Receptor (CAR) T cell therapy has revolutionized hematological cancer treatment, but its efficacy in solid tumors remains limited by the immunosuppressive and metabolically hostile tumor microenvironment (TME). CAR T cells’ functional compromise, exhaustion, and poor persistence are critically linked to their suboptimal metabolic fitness. This review highlights a paradigm shift: immunometabolism and its intricate interplay with epigenetics profoundly regulate T cell fate and function, establishing their reprogramming as a cornerstone for optimizing CAR T cell efficacy in diverse malignancies. We explore the intricate relationship between T cell differentiation and metabolic states, emphasizing that modulating CAR T cell metabolism ex vivo during manufacturing can drive differentiation towards less exhausted, more persistent memory phenotypes, such as stem cell central memory (Tscm) and central memory (Tcm) cells, which correlate with superior anti-tumor responses. Our analysis demonstrates that metabolic inhibitors offer significant potential to reprogram CAR T cells. Agents targeting glycolysis or the PI3K/Akt/mTOR pathway promote a memory-like phenotype by favoring oxidative phosphorylation (OXPHOS). Further strategies utilizing glutamine antagonists, mitochondrial modulators, or enzyme manipulation (e.g., IDH2, ACAT1) can epigenetically reprogram cells, fostering memory and exhaustion resistance. Similarly, nutrient level optimization during ex vivo expansion directly sculpts CAR T cell metabolic profiles. With approaches like glucose restriction/galactose substitution, or specific amino acid modulation (e.g., L-arginine, asparagine), persistence of CAR T cells in patients can be improved. The judicious selection and engineering of cytokines (e.g., IL-7, IL-15, IL-21) during manufacturing also plays a vital role in fostering desired memory phenotypes. In conclusion, metabolic engineering, leveraging its impact on epigenetic regulation during CAR T cell manufacturing, is crucial for generating potent, persistent, and functionally resilient products. This approach holds immense promise for expanding the curative potential of CAR T cell therapy to a broader range of cancers, particularly challenging solid tumors.